2012
DOI: 10.4103/1755-6783.98628
|View full text |Cite
|
Sign up to set email alerts
|

Multiple splenic abscesses in a child with enteric fever treated by percutaneous aspiration and antibiotics

Abstract: Multiple splenic abscesses are a condition associated with high mortality if there is delay in the diagnosis and initiation of specific treatment. Salmonella typhi as an etiological cause of multiple splenic abscesses is a distinct rarity. In the past treatment for splenic abscess including in enteric fever was splenectomy however; conservative treatment by percutaneous drainage is increasingly being reported for isolated splenic abscess and now for multiple splenic abscesses. We report a child with enteric fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…But only very few of them had multiple splenic abscesses. In India, R Chaudhari et al, Kirti M Naranje et al, and Sandeepkumar Kanwal et al, reported typhoid fever with multiple splenic abscesses [7,8,9]. The abscess which is caused by Salmonella tends to be associated with sickle cell disease, IV drug abusers, an impaired host resistance, subacute bacterial endocarditis, trauma , diabetes mellitus, urinary tract infections, skin sepsis, respiratory tract infections and immunodeficiency.…”
Section: Discussionmentioning
confidence: 99%
“…But only very few of them had multiple splenic abscesses. In India, R Chaudhari et al, Kirti M Naranje et al, and Sandeepkumar Kanwal et al, reported typhoid fever with multiple splenic abscesses [7,8,9]. The abscess which is caused by Salmonella tends to be associated with sickle cell disease, IV drug abusers, an impaired host resistance, subacute bacterial endocarditis, trauma , diabetes mellitus, urinary tract infections, skin sepsis, respiratory tract infections and immunodeficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous drainage is more preferable than surgical drainage due to the lack of postoperative complications, shorter hospital stay and lower treatment costs (13) . In the case of failure of any of these methods, partial or total splenectomy remains the standard, especially in multiple splenic abscesses (25% of cases) (15) . Although antibiotic therapy is an obligatory element of all these treatment modalities, it is not a substitute for invasive treatment.…”
Section: Discussionmentioning
confidence: 99%